Alternative design strategy and multi-material integration in the development of biologically-inspired soft robots: a proof-of-concept. (12th November 2020) - Romanò, Jacopo; Lazzari, Fabio; Garavaglia, Lorenzo; Pittaccio, Simone
Abstract: This study investigates the feasibility and consequences of using complex, nonlinear geometries in the manufacturing of soft robots actuated with shape memory alloys (SMAs). Anatomically-informed shaping of the functional elements was exploited to design the components of a finger-like soft robot. The SMAs were characterised and selected to provide the device actuation. This process involved thermo-mechanical tests to obtain material parameters for a finite element method model, which was then used to carry out a comparative analysis of different actuator shapes. Additive manufacturing and multi-material integration were then exploited to manufacture the device. The soft robot actuation was characterised using a combined thermal and motion-capture-based analysis. The paper presents a shape-mediated design strategy to obtain soft actuation in an integrated multi-material through the introduction of conjugated nonlinear shapes for the constituents and a spatially-changing relationship between their sections/stiffnesses.